(untitled) (MAUSAM, 2016)
A field experiment was conducted during kharif season of 2009 and 2010 in a sandy loam soil of New Delhi to study the effect of weather, achieved by sowing at normal (D1) and late (D2), on soil moisture prediction, evapotranspiration (ET), yield and water use efficiency (WUE) of three varieties (V1: JS 335, V2: Pusa 9712 and Pusa 9814) of soybean. Study of soybean phenology showed that there was reduction in the number of days taken for the crop to complete life cycle with delayed sowing. The agrometeorological water balance model could satisfactorily predict soil moisture content during soybean crop growth period with RMSE (%) varying between 6.27 to 12.06 and correlation coefficient between 0.828 to 0.982. The ET decreased significantly with delay in sowing; however there was no significant variation among the varieties. Among the stages of the soybean crop, mid season stage had highest ET followed by development stage, late season stage and initial stage. Normal sowing resulted in higher yield but lower WUE than the late sowing. Among the cultivars, JS 335 resulted in lower yield and WUE than Pusa 9712 and Pusa 9814. It may be recommended that, Pusa 9712 or Pusa 9814 may be sown during first and second week of July (normal sowing) to achieve higher yield in the semi-arid environment of Delhi region.